A method for the transfer function matrix of combined primary?secondary systems using classical modal decomposition. - Heredia-Zavoni, E. (Earthquake engineering & structural dynamics.)
Summer dreams... Summer's here, and the Wakefield twins can't wait to join Lila Fowler in fabulous, beach-lined Malibu. Elizabeth and Jessica have arranged jobs as mother's helpers and are looking forward to a dream vacation filled with Hollywood stars and gorgeous guys. But the girls soon find out things aren't always as they seem in sunny Malibu. Elizabeth's heart Is won by someone much too old for her. Even though she feels guilty about it, she begins to see him secretly. While Elizabeth tries desperately to keep her sister from finding out, Jessica is busy trying to get bronzed Cliff Sherman to notice her. Can the girls straighten out their summer romances, or will Malibu's magic be only an illusion?